2005
DOI: 10.1016/j.immuni.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Lamp-2a Facilitates MHC Class II Presentation of Cytoplasmic Antigens

Abstract: Extracellular antigens are internalized and processed before binding MHC class II molecules within endosomal and lysosomal compartments of professional antigen presenting cells (APC) for subsequent presentation to T cells. Yet select cytoplasmic peptides derived from autoantigens also intersect and bind class II molecules via an unknown mechanism. In human B lymphoblasts, inhibition of the peptide transporter associated with antigen processing (TAP) failed to alter class II-restricted cytoplasmic epitope prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
262
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(272 citation statements)
references
References 43 publications
4
262
4
1
Order By: Relevance
“…The CMA machinery, including heat shock cognate protein of 70 kDa (hsc70) that selects peptide substrates, and multimeric lysosomal-associated membrane protein 2A (LAMP-2A) complex, facilitates the entry of peptide into the lysosome (Orenstein and Cuervo, 2010;Li et al, 2011b). MHCII antigen presentation of cytosolic glutamate decarboxylase in human B lymphoblastoid cells is reduced following knockdown of LAMP-2 or hsc70 (Zhou et al, 2005). In addition, overexpression of LAMP-2A or hsc70 increases MHCII presentation of cytosolic glutamate decarboxylate.…”
Section: Autophagy In Mhc Class II Antigen Presentationmentioning
confidence: 99%
“…The CMA machinery, including heat shock cognate protein of 70 kDa (hsc70) that selects peptide substrates, and multimeric lysosomal-associated membrane protein 2A (LAMP-2A) complex, facilitates the entry of peptide into the lysosome (Orenstein and Cuervo, 2010;Li et al, 2011b). MHCII antigen presentation of cytosolic glutamate decarboxylase in human B lymphoblastoid cells is reduced following knockdown of LAMP-2 or hsc70 (Zhou et al, 2005). In addition, overexpression of LAMP-2A or hsc70 increases MHCII presentation of cytosolic glutamate decarboxylate.…”
Section: Autophagy In Mhc Class II Antigen Presentationmentioning
confidence: 99%
“…However, recent studies have revealed that CMA is involved in antigen processing and presentation. The levels of autoantigen presentation are closely related to CMA activity [45][46][47] .…”
Section: Molecular Mechanisms Of Cmamentioning
confidence: 99%
“…However, recent studies have revealed that CMA is involved in antigen processing and presentation. The levels of autoantigen presentation are closely related to CMA activity [45][46][47] .As the two major proteolytic systems mediating the degradation of intracellular proteins [48,49] , the ALP and the UPS are not isolated and independent but tightly coordinated. CMA may affect the UPS and the other two autophagic pathways, and the UPS and the other two autophagic pathways can also modulate CMA activity.…”
mentioning
confidence: 99%
“…33,40 For this pathway, peptides seem to be imported directly into endosomal/lysosomal compartments, via a transporter that was recently suggested to be Lamp-2a, the transporter of chaperone-mediated autophagy. 47 In addition to these proteasome-dependent pathways, cytosolic and nuclear proteins can also be processed by a proteasome-and TAPindependent pathway: This fourth pathway involves the direct import of cytosolic/nuclear proteins (e.g. the EBV nuclear antigen 1 (EBNA1) 30,31 ) into endosomes/lysosomes and is in part mediated by autophagy.…”
Section: Endogenous Mhc Class II Processingmentioning
confidence: 99%
“…It is thought that peptides are directly imported into endosomal/lysosomal compartments via a peptide transporter, possibly Lamp-2a. 47 (4) Cytosolic and nuclear proteins (e.g. the EBV nuclear antigen 1 (EBNA1) 31 ) can be processed by lysosomal proteases after direct import into endosomal/lysosomal compartments failed to be detected by M1-specific CD4 þ T cells, but stimulated M1-specific CD8 þ T cells.…”
Section: Proteasome-and Tap-independent Processing Of Cytosolic and Nmentioning
confidence: 99%